Three metamorphic events recorded in a single garnet: Integrated phase modelling, in situ LA-ICPMS and SIMS geochronology from the Moine Supergroup, NW Scotland - Cutts, K.; Kinny, Peter; Strachan, R.; Hand, M.; Kelsey, D.; Emery, M.; Friend, C.; Leslie, A. (Blackwell Publishing, 2010)
In situ LA-ICP-MS monazite geochronology from a garnet-bearing diatexite within the Moine Supergroup (Glenfinnan Group) NW Scotland records three temporally distinct metamorphic events within a single garnet porphyroblast. The initial growth of garnet occurred in the interval c. 825–780 Ma, as recorded by monazite inclusions located in the garnet core. Modelled P–T conditions based on the preserved garnet core composition indicate an initially comparatively high geothermal gradient regime and peak conditions of ∼650 °C and 7 kbar. Monazite within a compositionally distinct second shell of garnet has an age of 724 ± 6 Ma. This is indistinguishable from a SIMS age of 725 ± 4 Ma obtained from metamorphic zircon in the sample, which is interpreted to record the timing of migmatization. This second stage of garnet growth occurred on a P–T path from ∼6 kbar and 650 °C rising to ∼9 kbar and 700 °C, with the peak conditions associated with partial melting. A third garnet zone which forms the rim contains monazite with an age of 464 ± 3 Ma. Monazite in the surrounding matrix has an age of 462 ± 2 Ma.This corresponds well with a U–Pb SIMS zircon age of 463 ± 4 Ma obtained from a deformed pegmatite that was emplaced during widespread folding and reworking of the migmatite fabric. The P–T conditions associated with the final phase of garnet growth were ∼7 kbar and 650 °C. The monazite ages coupled with the phase relations modelled from this multistage garnet indicate that it records two Neoproterozoic tectonothermal events as well as the widespread Ordovician Grampian event associated with Caledonian orogenesis. Thus, this single garnet records much of the Neoproterozoic to Ordovician thermal history in NW Scotland, and highlights the long history of porphyroblast growth that can be revealed by in situ isotopic dating and associated P–T modelling. This approach has the potential to reveal much of the thermal architecture of Neoproterozoic events within the Moine Supergroup, despite intense Caledonian reworking, if suitable textural and mineralogical relationships can be indentified elsewhere.